A Formação Continuada do Professor da EJA/Fase I para o Ensino de Ciências: Um Olhar para Cascavel/PR - Wielewski, Jaqueline Miliavaca (2019)
Continuing Education is an activity inherent to teachers’ profession, which allows an ongoing learning to this professional. Regarding Continuing Education of Science for Youth and Adult (EJA) specificity - Phase I, focus of this research, it becomes even more relevant due to the inceptive background both in Science and in EJA specificities. Thus, this research discusses about the following questions: with what profile and frequency is the Specific Continuing Education taking place to act out in Youth and Adult Education (EJA) in Cascavel city? Has this training, according to the teachers’ point of view, contributed to pedagogical practice, to teachers’ autonomy training and science teaching development? This study used bibliographic review, documentary research and field research. In documentary research, documents of the Ministry of Education (MEC), as well as the Municipal Education Department (SEMED) of Cascavel/PR, were analyzed, which helped to understand the proposed subject. And, in order to develop the field research, 18 teachers were interviewed from EJA classes - Phase I, from Cascavel city, as well as coordinators of SEMED, responsible for EJA and Sciences discipline. The interviews were audio-recorded to verify the profile of Continuing Education in the city and the studied teachers’ perception regarding training. Data were analyzed according to the Content Analysis method and indicate that these teachers considered the Specific Continuing Education in Sciences and Youth and Adult Education as of utmost importance for the pedagogical practice. It was also observed that the Continued Training offered by SEMED has been scarce, according to the interviewed teachers. Thus, there is a negative reflection on the teachers’ action. The intentionality of the Continuing Education offered comes for the teacher to understand that schooling has contributed significantly to the achievement of the development level to improve life quality